The General Concept of Diplomatic Immunity Abuse (A comparative study) - Abdul-Hussein , Researcher. Intisar; Saadoun Al-Abadi , Assist. Prof. Dr. Osama (Basra studies journal, 2023)
The general concept of diplomatic immunity abuse is one of the most critical issues that affect the security of the host country when diplomatic envoys misuse the diplomatic immunity granted to them in light of the Vienna Convention on Diplomatic Relations of 1961. Diplomatic envoys exploiting their immunity and using it as a justification for committing abuses lead to situations far from the legal legitimacy for which immunity was granted. Therefore, we divided the research into two sections, addressing in the first section the concept of diplomatic immunity abuse, and in the second section, the forms of diplomatic immunity abuse.